The Development of IPA Tutoring PENGEMBANGAN PAKET BIMBINGAN BELAJAR IPA BAGI PESERTA DIDIK SMP NEGERI 6 TERNATE - Mita, Rasmita Sabtu; H. Taunaumang; Orbanus Naharia (Jurnal Lingkungan Almuslim, 2023)
Abstract,This research is the development research by the following steps: (1) Research and initial data collection, (2) planning, (3) Preparation of Initial Product, (4) initial tests. (5) Repair initial products, (6) The field trials, (7) Improvement of operational products, (8) Test operations, (9) Improved end products, (10) Product Dissemination. The data source in this study consists of 3 experts of product design and including a material expert. And there are 40 students who divided into two classes, 20 students in the class IX-3 as the control class and the others 20 students in the class IX-1 as the experimental class in SMP Negeri 6 Ternate. The purpose of this research is to develop IPA tutoring package and to increase the study results of the students after tutoring. The test results shows the development of IPA tutoring package is very well and worth used in tutoring with the results of 80% and product design test result has reached 83% with a very decent qualitfications and categories very well. For the study result of students at the operational test reveals that there is a different average in learning outcomes of students who use IPA tutoring package to learn and do not use the package. This is evidenced by sig.2-Tailed value < 0.05 where the value of 0.00 <0.05. The results of teacher responses in operational tests of the IPA tutoring package is very well with a percentage of 98%. Then the results of the students responses to learn IPA tutoring package is very good as well with the percentage of 91%. This research has resulted that IPA Tutoring Package facilitate teachers and students to learn better.